Essays on economic growth diagnostic and demographics in Sub-Saharan Africa - (:unkn) unknown (My University, 2020)
Our research shows that demographic growth and structure are significant determinants of economic growth in Sub Saharan Africa. Therefore, we suggest that the HRV framework should be augmented to include an analysis on demographic growth and structure, allowing a comprehensive approach on the binding constraints on economic growth of a given country in Sub Saharan Africa.
Keywords: African Research